2007
DOI: 10.3892/or.18.5.1329
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phospholipase D2 in human colorectal carcinoma

Abstract: Abstract. Phospholipase D (PLD) catalyzes the hydrolysis of phosphatidylcholine (PC) to generate phosphatidic acid (PA) and choline. PA acts as a second messenger in cell proliferation; therefore PLD is believed to play an important role in carcinogenesis. PLD activity has been reported to be elevated in human breast, gastric, renal cell and colorectal carcinomas, compared with adjacent non-neoplastic tissues. The activity of PLD was also correlated with nuclear grade in breast cancer, tumor size in gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Participation of PLD-generated PA in downstream signal transduction from mitogenic growth factor receptors via Ras and the MAP kinase pathway has been demonstrated. 12 In comparison with adjacent non-neoplastic tissues, elevated expression and activity of PLD have been detected in various human tumors, including those of breast, 7,31 colorectal, 32,33 gastric, 34 renal 35 and papillary thyroid cancers. 36 Recent clinical studies have reported on correlation of PLD expression levels with tumor size; an association with survival of patients with colorectal carcinoma was also reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation of PLD-generated PA in downstream signal transduction from mitogenic growth factor receptors via Ras and the MAP kinase pathway has been demonstrated. 12 In comparison with adjacent non-neoplastic tissues, elevated expression and activity of PLD have been detected in various human tumors, including those of breast, 7,31 colorectal, 32,33 gastric, 34 renal 35 and papillary thyroid cancers. 36 Recent clinical studies have reported on correlation of PLD expression levels with tumor size; an association with survival of patients with colorectal carcinoma was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recent clinical studies have reported on correlation of PLD expression levels with tumor size; an association with survival of patients with colorectal carcinoma was also reported. 32 A sustained and increased level of PLD can be deleterious and can contribute to the development of cancer. 37 Because of its important role in progression of cancer, PLD could be a target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression and elevated activity of PLD result in cellular transformation and has been implicated in multiple human cancers including colorectal (Saito et al, 2007;Kang et al, 2008), breast (Noh et al, 2000), renal (Zhao et al, 2000), gastric carcinoma (Uchida et al, 1999), and thyroid cancers . Stable cells overexpressing PLD1 and PLD2 demonstrate anchorage-independent growth and tumorigenesis in nude mice (Min et al, 2001;Buchanan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above in cell growth signaling, PLD2 and PA can both directly affect mTor signaling, which is a main target of anti-cancer drugs, for example, rapamycin (a competitor of PA) is being used for tumor treatment. In addition, the expression level and activity of PLD2 have been reported to be elevated in several cancers, including colorectal cancer and renal cancer (Zhao et al, 2000;Saito et al, 2007), and to be associated with tumor size and survival (Saito et al, 2007). Furthermore, a PLD2 polymorphism detected in colorectal cancer was found to be closely linked to the prevalence of the disease (Wood et al, 2007).…”
Section: Notementioning
confidence: 96%
“…Vessel occlusioninduced hypoxia in the hippocampus has been reported to increase PLD2 levels (Min do et al, 2007). Furthermore, the expression of PLD2 is known to be significantly elevated in many cancers, including breast, renal, and colon cancer (Zhao et al, 2000;Saito et al, 2007;Wood et al, 2007).…”
Section: Expressionmentioning
confidence: 99%